CsWAK12, a novel cell wall-associated receptor kinase gene from Camellia sinensis, promotes growth but reduces cold tolerance in Arabidopsis - Wu, Qiong; Jiao, Xiaoyu; Liu, Dandan; Sun, Minghui; Tong, Wei; Ruan, Xu; Wang, Leigang; Ding, Yong; Zhang, Zhengzhu; Wang, Wenjie; Xia, Enhua (Frontiers in Plant Science, 2024)
Cold significantly impacts the growth and development of tea plants, thereby affecting their economic value. Receptor-like kinases (RLKs) are thought to play a pivotal role in signaling the plant's response to cold and regulating cold tolerance. Among the RLK subfamilies, wall-associated receptor-like kinases (WAKs) have been investigated across various plant species and have been shown to regulate cell growth and stress responses. However, the function of WAK genes in response to cold stress in tea has yet to be studied. In a previous investigation, we identified the WAK gene family from Camellia sinensis and isolated a specific WAK gene, CsWAK12, which is induced by abiotic stresses. Here, we demonstrate that CsWAK12 is involved in the regulation of cold tolerance in tea plants. CsWAK12 was rapidly induced by cold, peaking at 3 hours after treatment at 4°C (10-fold increase). Heterologous overexpression of CsWAK12 (35S:CsWAK12) in Arabidopsis promoted plant growth by enhancing root length and seed size under normal conditions, although it reduced cold resistance compared to the wild type. Under cold stress, the transgenic plants exhibited a lower survival rate and significantly altered levels of superoxide dismutase (SOD) activity and malondialdehyde (MDA) content compared to the wild type (WT). Furthermore, the expression of C-repeat/dehydration-responsive element binding factor (CBF) genes was diminished in CsWAK12-overexpressing transgenic Arabidopsis plants following cold treatment. Transcriptome analysis revealed that genes associated with the CBF pathway, such as transcription factor genes (ERF53, ERF54, and DREB2A) were markedly reduced in the overexpression line. These data suggest that CsWAK12 acts as a negative regulator, reducing the cold tolerance of transgenic Arabidopsis by mediating the CBF pathway. Therefore, CsWAK12 may serve as a candidate gene for the molecular breeding of cold resistance in tea plants.